Source and health risks of trace metals in Clarias batrachus and Chrysichthys nigrodigitatus from surface waters in Bayelsa State, Nigeria: a probabilistic model - Izah, Sylvester Chibueze; Richard, Glory; Stanley, Herbert Okechukwu; Sawyer, Wisdom Ebiye; Uwaeme, Onyebuchi Remy; Sylva, Ligeiaziba (Frontiers in Sustainable Food Systems, 2024)
Human activities have inadvertently led to the release of harmful substances, including trace metals, into aquatic environments, with consequential impacts on aquatic organisms and potential health risks for consumers. This research assessed the presence, origins, and health implications of trace elements within the muscles of Clarias batrachus and Chrysichthys nigrodigitatus fish species from the Bomadi and Gbotebo rivers and their surroundings in Bayelsa State, Nigeria.Thirty samples from each fish species were collected and analyzed to conduct the study. Through the use of an atomic absorption spectrophotometer, the researchers determined the concentrations of both macronutrients (such as calcium, magnesium, sodium, and potassium) and micronutrients (trace metals including iron, copper, zinc, lead, nickel, cadmium, and cobalt) in the fish tissues. This enabled a comprehensive assessment of potential risks posed by these elements. The concentrations of the metalselements within the two fish species varied, with notable differences in zinc and, cadmium, magnesium, and calcium levels. Utilizing statistical analyses like Pearson correlation, principal component analysis (PCA), and hierarchical cluster analysis (CA), it was established that the trace elements metals originated from diverse sources. The study then evaluated health risks associated with these trace elements, considering both non-carcinogenic and carcinogenic hazards for different age groups. The results indicated that children's total target hazard quotient fell below 1 for both fish species, implying a limited tendency towards noncarcinogenic risks through lifelong fish consumption. However, in some adult fish samples, the quotient exceeded 1, indicating a higher potential for non-carcinogenic risks. Regarding carcinogenic hazards, the mean risks were generally lower than the accepted threshold, except for lead in both fish species among adults and children. Stricter values highlighted that only lead concentrations in fish from both categories were deemed acceptable. Consequently, this study underscores highlights the importance of raising awareness among consumers who buy fish from the studied region. Moreover, consistent monitoring of potentially harmful trace elements in water, sediments, and fish is recommended to safeguard consumer health and well-being.